How to Start a Food Business: Introduction - Soohyoun Ahn; Renee Goodrich-Schneider; Amarat H. Simonne (EDIS)
While running your own food business can be a rewarding and exciting experience, it can be overwhelming and stressful. It is important to understand the pros and cons of running your own food business and decide if you are ready to pursue a food business venture. This 3-page fact sheet was written by Soohyoun Ahn, Renee Goodrich-Schneider, and Amarat H. Simonne, and published by the UF Department of Food Science and Human Nutrition, September 2014.